Airway clearance techniques used by people with cystic fibrosis in the UK. Issue 4 (December 2015) - Hoo, Z.H.; Daniels, T.; Wildman, M.J.; Teare, M.D.; Bradley, J.M.
Abstract: Objectives: To describe the current use of airway clearance techniques among people with cystic fibrosis (CF) in the UK, and the baseline characteristics for users of different airway clearance techniques. Design: Analysis of the UK CF Registry 2011 data. Setting and participants: All people with CF in the UK aged ≥11 years ( n = 6372). Results: Of the 6372 people on the UK CF registry in 2011, 89% used airway clearance techniques. The most commonly used primary techniques were forced expiratory techniques (28%) and oscillating positive expiratory pressure (PEP) (23%). Postural drainage and high-frequency chest wall oscillation were used by 4% and 1% of people with CF, respectively. The male:female ratio of individuals who used exercise as their primary airway clearance technique was 2:1, compared with 1:1 for other techniques. Individuals with more severe lung disease tended to use devices such as non-invasive ventilation or high-frequency chest wall oscillation. Conclusions: Forced expiratory techniques and oscillating PEP are the most common airway clearance techniques used by people with CF in the UK, and postural drainage and high-frequency chest wall oscillation are the least common techniques. This is significant in terms of planning airway clearance technique trials, where postural drainage has been used traditionally as the comparator. The use of airway clearance techniques varies between countries, but the reasons for these differences are unknown.